Facing complexity through varying the clarification of the design task: How a multi-contextual approach can empower design engineers to address complex challenges - Kersten, Wouter Carel; Diehl, Jan Carel; van Engelen, Jo M.L. (FormAkademisk, 2018)
Today, most challenges designers face are complex. One way industrial design engineers have learned to deal with this complexity is to simplify the problem early on—for example, by focusing on one particular context, e.g. user group. Variations are typically addressed, but preferably inside the simplified design task or even after initial success has been achieved and a path has been set out. A range of authors have suggested ways to address variations during the design process. This paper contributes to exploring this notion of variation by presenting an approach that emphasises contextual variation early on, clarifying the design task before the design process, in a narrow sense, begins. This enables designers to seize opportunities that reveal themselves before a final path is set. Based on real-life cases and discussion of existing literature, the value of this approach for an industrial designer’s arsenal is explored and guidance for next steps is offered. Keywords: context variation, complexity, design arsenal, variation of the design task, design approach